2015
DOI: 10.3319/tao.2014.08.19.01(grt)
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the March 27, 2013 M 6.2 Earthquake Hypocenter Using Momentary High-Conductivity Materials

Abstract: Seismo-magnetic anomalies induced from the momentary existence of current and/or high-conductivity materials have been widely reported. The Parkinson vectors derived from 3-component geomagnetic data at 3 stations were obtained via the magnetic transfer function and discussed with respect to the location (23.90°E, 121.07°N) and the depth (15.1 km) of the M 6.2 earthquake on March 27, 2013 in Taiwan. Azimuth distribution constructed from the entire Parkinson vectors during the observation period is utilized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Similarly, the reoccurrence of a significant increase in soil radon concentrations was found ∼2 weeks before the 2020/02/06 M6.6 Meinong earthquake (EQ-26) in southern Taiwan, and a substantial POEA occurred following the radon anomalies 9-12 days before the EQ-26 event (Fu et al, 2017a). Furthermore, Chen et al (2015a) reported that the high-conductivity materials were enhanced ∼12-13 days before the M6.2 2013/03/27 Nantou earthquake (EQ-14) and…”
Section: Relationship Between Olr E Index Variations and Seismicitymentioning
confidence: 95%
“…Similarly, the reoccurrence of a significant increase in soil radon concentrations was found ∼2 weeks before the 2020/02/06 M6.6 Meinong earthquake (EQ-26) in southern Taiwan, and a substantial POEA occurred following the radon anomalies 9-12 days before the EQ-26 event (Fu et al, 2017a). Furthermore, Chen et al (2015a) reported that the high-conductivity materials were enhanced ∼12-13 days before the M6.2 2013/03/27 Nantou earthquake (EQ-14) and…”
Section: Relationship Between Olr E Index Variations and Seismicitymentioning
confidence: 95%
“…Niu (2000) used the sudden changes of crust deformation at various stations to predict the location of the epicenter of an earthquake in China. Chen et al (2015aChen et al ( , 2015b using momentary high-conductivity materials to estimate the hypocenter for earthquakes in Taiwan. The concept stated above expresses that the stress (or strain) caused by earthquakes should be related to the earthquake magnitude and epicentral distance.…”
Section: Introductionmentioning
confidence: 99%